KESETARAAN DAN KEADILAN GENDER DALAM PANDANGAN PEREMPUAN BALI: STUDI FENOMENOLOGIS TERHADAP PENULIS PEREMPUAN BALI - Widayani, Ni Made Diska; Hartati, Sri (Jurnal Psikologi, 2014)
AbstractThis study aims to describe the perception of Balinese women towards gender equality and justice (GEJ) concepts within the scope of Balinese culture. This is a qualitative-phenomenological study. Subjects were defined based on literature review that resulted three women participated in this study. Depth interview and semi-participant observation was used to collect data. The results showed that GEJ was interpreted differently by each subject. Subject 1 perceived patriarchal culture of Bali is a gender-equitable culture, while Subject 2 and 3 perceived patriarchal culture of Bali is not a gender-equitable culture. To what extent subjects resolved their problems related to the patriarchal culture of Bali in the past impacted their perception on gender equality and justice. Their perception on GEJ were influenced by external factors (such as Balinese culture, educational level, parenting) as well as internal factors (such as needs, attitudes, self-concept, conformity, beliefs, future expectation, value of Balinese women, families and children; resistance as a manifestation of problems encountered by each subject; and social support as a supporting factor that help subjects to resolve their problems).